Sistem Pendukung Keputusan Pemilihan Pemasok Bahan Baku Menggunakan Metode PROMETHEE - Raditya Rimbawan Oprasto (Jurnal Media Celebes, 2023)
The decision-making system is at the core of the management process in any organization. It includes the collection, analysis, and evaluation of information to select appropriate actions in achieving predefined goals. The PROMETHEE (Preference Ranking Organization METHod for Enrichment Evaluation) method is a mathematical approach used to support multi-criteria decision making. This method is used to compare alternatives based on several different criteria, resulting in a ranking of alternatives based on the level of preference or importance given to each criterion. This study aims to provide recommendations to companies selecting the best raw material suppliers using the PROMETHEE method, so that companies get recommendations on performance from existing raw material suppliers. The results of the supplier selection ranking for raw materials that get Rank 1 are Supplier B with a value of 0.83, Rank 2 is Supplier C with a value of 0.33, Rank 3 is Supplier A with a value of -1.17.